2011
DOI: 10.1530/eje-10-0879
|View full text |Cite
|
Sign up to set email alerts
|

A case of primary aldosteronism in pregnancy: do LH and GNRH receptors have a potential role in regulating aldosterone secretion?

Abstract: Objective: The mechanisms inducing steroidogenesis in primary aldosteronism (PA) remain poorly defined. It was recently demonstrated that some G-protein-coupled receptors are abnormally expressed in aldosterone-producing adenomas (APA). We evaluated the potential role of LH and GNRH receptors (LHR (or LHCGR) and GNRHR) in regulating aldosterone secretion in a patient with APA arising during pregnancy (index case) and in a subset of other patients with PA. Patients and methods: GNRH test was performed in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 30 publications
5
29
1
Order By: Relevance
“…The immunopositivities were found in the cell membrane as well as the cytoplasm, compatible with a previous report (Albiger et al , 2011; Xing et al ., 2009). Immunohistochemical analysis revealed that GnRHR positive tumor cells were sparsely distributed in APA, and the mean ratio of the positive cells was approximately 10% in the whole tumor area of the cases examined (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…The immunopositivities were found in the cell membrane as well as the cytoplasm, compatible with a previous report (Albiger et al , 2011; Xing et al ., 2009). Immunohistochemical analysis revealed that GnRHR positive tumor cells were sparsely distributed in APA, and the mean ratio of the positive cells was approximately 10% in the whole tumor area of the cases examined (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…During pregnancy, hypertension and symptoms may improve (49,210,424). This is thought to be due to the anti-mineralocorticoid effects of high circulating levels of placental progesterone, which antagonize aldosterone action at the MR. On the other hand, several case reports exist of PA presenting during pregnancy (17,127,466,518). In one of these (518), APAs from both affected patients harbored somatic mutations in CTNNB1, encoding ␤-catenin in the Wnt celldifferentiation pathway (which may in part explain tumor development).…”
Section: Symptoms and Signs Of Pamentioning
confidence: 99%
“…Furthermore, in vivo and in vitro studies in patients with PA showed that aldosterone secretion was aberrantly regulated by several GPCRs albeit with substantial diversity of the receptors involved; of interest, aldosterone hypersecreting tissues exhibited ectopically expressed GNRH (4/15) and thyroid-releasing hormone (TRH) (1/15) mRNA that correlated with in vivo responses in a subset of patients studied (18,51,54). In favour of the role of these receptors are cases of PA that developed during pregnancy and were responsive to LH stimulation (63). The notion that the expression of aberrant receptors may be directly involved in the pathogenesis of PA is attractive as treatment targeting such receptors could have a therapeutic effect.…”
Section: Evidence In Favour Of An Acth Role In Aldosterone Regulationmentioning
confidence: 99%